The one and only Bob - Applegate, Katherine; Castelao, Patricia (New York : Harper, 2020)
Bob sets out on a dangerous journey in search of his long-lost sister with the help of his two best friends, Ivan and Ruby. As a hurricane approaches and time is running out, Bob finds courage he never knew he had and learns the true meaning of friendship and family.
Sequel to the One and Only Ivan.
Keywords: Dogs -- Juvenile fiction; Gorilla -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction